Processed ship-based Navigation Data from the Amundsen Sea acquired during the Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2009)
This data set was acquired with a ship-based Navigation system during Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs). These data files are of MGDS:Nav format and include Primary Navigation data and were processed after data collection. Data were acquired as part of the project(s): The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by NSF grant(s): ANT04-40775.